An empirical study of debt-equity ratios in retail and construction industries - Ang, Geok Sim (2013)
This report presents the findings of an empirical study on the debt-equity ratios of the retail and construction companies in Singapore. This study attempts to relate finance theories with real life evidence in the Singapore context.